CLAIMS WORK LEGAL SERVICES ENTITIES OF BUSINESS ENTITIES - Kozyreva, Valentyna P.; Milimko, Larysa V. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article is focused on the analysis of the claims settlement procedures with the aim to provide the effective and appropriate work conditions of the enterprise. The role, content and the significance of the claims management by the law departments and the propositions to its improvement are under the study.